The 'safe death': An ethnographic study exploring the perspectives of rural palliative care patients and family caregivers. (December 2018) - Rainsford, Suzanne; Phillips, Christine B; Glasgow, Nicholas J; MacLeod, Roderick D; Wiles, Robert B
Background: In rural settings, relationships between place and self are often stronger than for urban residents, so one may expect that rural people would view dying at home as a major feature of the 'good death'. Aim: To explore the concept of the 'good death' articulated by rural patients with life-limiting illnesses, and their family caregivers. Design: Ethnography, utilising open-ended interviews, observations and field-notes. Participants: In total, 12 rural (town and farm) patients with life-limiting illnesses, 18 family caregivers and 6 clinicians, in the Snowy Monaro region of New South Wales, Australia, participated in this study over the course of the deaths of the patients. Interviews were transcribed and analysed with observational data using an emergent thematic process. Results: A 'safe death' was central to a 'good death' and was described as a death in which one could maintain (1) a connection with one's previous identity; (2) autonomy and control over decisions regarding management of end-of-life care and (3) not being overwhelmed by the physical management of the dying process. For all participants, the preferred place of death was the 'safe place', regardless of its physical location. Conclusion: Safety, in this study, is related to a familiar place for death. A home death is not essential for and does not ensure a 'good death'. We all have a responsibility to ensure all places for dying can deliver the 'safe death'. Future research could explore the inter-relationships between safety and preference for home or home-like places of death.